2020
DOI: 10.1016/j.immuni.2020.06.011
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-wide CRISPR Screen Reveals a Role for the Non-canonical Nucleosome-Remodeling BAF Complex in Foxp3 Expression and Regulatory T Cell Function

Abstract: Highlights d Genome-wide CRISPR screen identifies Foxp3 regulators in primary regulatory T cells d A SWI/SNF variant, the Brd9-containing ncBAF complex, regulates Foxp3 expression d Foxp3 binding to a subset of its target genes is dependent on co-binding of Brd9 d Brd9 deficiency in Treg exacerbates IBD and enhances antitumor immunity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 65 publications
(50 reference statements)
1
71
1
Order By: Relevance
“…Recent research has identified a role for BRD9 in regulatory T-cell (Treg) development via control of Foxp3 [ 67 ], a TF known to coordinate differentiation and functional events in Tregs [ 68 ]. Loo et al showed that GBAF promoted the expression of Foxp3 , an observation in contrast to the repressive effects on Fox3p by PBAF.…”
Section: Gbaf and Its Subunits In Mammalian Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has identified a role for BRD9 in regulatory T-cell (Treg) development via control of Foxp3 [ 67 ], a TF known to coordinate differentiation and functional events in Tregs [ 68 ]. Loo et al showed that GBAF promoted the expression of Foxp3 , an observation in contrast to the repressive effects on Fox3p by PBAF.…”
Section: Gbaf and Its Subunits In Mammalian Developmentmentioning
confidence: 99%
“…Loo et al showed that GBAF promoted the expression of Foxp3 , an observation in contrast to the repressive effects on Fox3p by PBAF. Furthermore, the authors demonstrated that BRD9 chemical degradation or ablation of Brd9 compromised Treg function in both in vitro and in vivo conditions [ 67 ]. These results are especially relevant to the search for therapeutic targets for immune system control in autoimmune diseases and cancers; the links between T-cell function and GBAF suggest a potentially viable target in this pursuit.…”
Section: Gbaf and Its Subunits In Mammalian Developmentmentioning
confidence: 99%
“…Targeting multiple genomic loci with site-specific nucleases allows multiplexing of gene knockouts (KOs) in a single intervention. Two recent manuscripts described CRISPR/Cas9 KO screening in Tregs to define genes involved in mouse Treg stability and function ( 63 , 81 ).…”
Section: Genetic Engineering Tools For the Generation Of Super-tregmentioning
confidence: 99%
“…Histone deubiquitination by Usp22 and Atxn7l3 promotes FOXP3 expression, contrary to CHIP1 and DBC1. Chromatin remodeling by BRD9, a member of the SWI/SNF chromatin remodeling complex, positively regulates FOXP3 as BRD9 depletion reduces the binding of FOXP3 to its enhancers CNS2/CNS0, thereby reducing FOXP3 expression ( 63 ). BRD9 also regulates a subset of FOXP3 target genes by promoting both FOXP3 binding at their regulatory element and increasing histone modifications.…”
Section: Genetic Engineering Strategies For Enhanced Stability and Fumentioning
confidence: 99%
“…For instance, three recent studies have used genome-wide and pooled Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) screen approaches, to identify unknown elements involved in the maintenance of Foxp3 expression and Treg cell identity both in murine and human cells [128][129][130]. These reports have highlighted a series of novel pathways, such as ubiquitin ligases and deubiquitinases, chromatin remodelers, and transcription factors; in particular, Loo et al nicely demonstrated that ablation of the Bromodomain-containing protein 9 (Brd9) subunit of the non-canonical BRG1/BRM Associated Factors (BAF) complex, impaired Foxp3 expression and reduced Treg cell function, leading to enhanced tumor immunity and delayed growth of transplanted MC38 colon adenocarcinoma cells [129]. The quantity of data brought by modern technologies such as CRISPR screens will be invaluable for the discovery of unique or shared molecules that can be targeted to impair Treg cells specifically in tumors.…”
Section: Missing Pieces Of the Puzzlementioning
confidence: 99%